Summer thermal performances of PCM-integrated insulation layers for light-weight building walls: Effect of orientation and melting point temperature. (June 2018) - Fateh, Amirreza; Borelli, Davide; Devia, Francesco; Weinläder, Helmut
Graphical abstract: Highlights: Multilayer-plane wall, integrated with phase change materials (PCMs). Modelling non-linear thermal behaviour of PCMs embedded in novel insulation layers. Thermal hysteresis in circadian temperature oscillation. Effect of solar radiation on PCM-based thermal insulation layer efficacy. Analysis of effects of PCM-based thermal insulation layer position inside of the wall. Abstract: Phase change materials (PCMs) as insulation layers constitute a novel application of this kind of heat storage materials, which could be profitably used in buildings for energy saving because they can shave the peak heating load during the day. PCMs exploit the capability of storing and releasing the latent heat of phase change with minor or even no variation of temperature. In this condition, they show an apparent increase of their thermal capacity, per unit of mass or volume, which can be particularly useful in lightweight walls. This paper deals with the effect of solar radiation on a light-wall with PCM-integrated. In addition, a dynamic model of a wall is developed considering the different conditions such as position of PCM and different orientation of the wall. The results show that utilizing PCMs integrated insulation layers could provide major reductions of heat loads when their intensity is fluctuating and variable, and that this solution is more effective when the temperature variations are close to the phase change temperature, leading to energy savings up to 75% of the heat load through opaque walls.